2001
DOI: 10.1046/j.0022-3042.2001.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of inflammation‐ and apoptosis‐related genes in spinal cords of a mutant SOD1 transgenic mouse 
model of familial amyotrophic lateral sclerosis

Abstract: Familial amyotrophic lateral sclerosis (FALS)-linked mutations in copper±zinc superoxide dismutase (SOD1) cause motor neuron death through one or more acquired toxic properties. We analyzed the molecular mechanism underlying motor neuron degeneration in the transgenic mouse model expressing the SOD1 gene with G93A mutation. Using cDNA microarray, the differentially expressed genes were identi®ed in the spinal cords of G93A mice, 30 being elevated and seven decreased. cDNA microarray analysis to monitor gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
186
2
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(203 citation statements)
references
References 45 publications
12
186
2
3
Order By: Relevance
“…Because certain aspects of ALS are non-cell autonomous and originate from mutant SOD1 accumulation in non-motor neuronal cells (8,9), cell-type specificity is of high importance when using such an approach. To date, three main gene-expression profiling studies have been reported (10)(11)(12), all of which were restricted to analysis of the adult disease phase in one SOD1 mouse line that accumulates a dismutase active mutant to extraordinarily high levels during disease progression [between 10-and 20-fold over the already abundant endogenous mouse SOD1 (4,13)]. Two studies (10,11) used the entire spinal cord, thus losing cell-type specificity and masking mRNA changes within motor neurons as a consequence of the much more numerous glial cells and their activation before or during disease progression.…”
mentioning
confidence: 99%
“…Because certain aspects of ALS are non-cell autonomous and originate from mutant SOD1 accumulation in non-motor neuronal cells (8,9), cell-type specificity is of high importance when using such an approach. To date, three main gene-expression profiling studies have been reported (10)(11)(12), all of which were restricted to analysis of the adult disease phase in one SOD1 mouse line that accumulates a dismutase active mutant to extraordinarily high levels during disease progression [between 10-and 20-fold over the already abundant endogenous mouse SOD1 (4,13)]. Two studies (10,11) used the entire spinal cord, thus losing cell-type specificity and masking mRNA changes within motor neurons as a consequence of the much more numerous glial cells and their activation before or during disease progression.…”
mentioning
confidence: 99%
“…Two independent studies using microarray analysis of transgenic mice expressing the human FALS-associated G93A SOD1 mutant (24,25) and microarray analysis of human ALS spinal cord (26) have detected some characteristic gene expression changes. Differential regulation of apoptosis-, inflammation-, and antioxidantrelated genes were findings common to all of these studies.…”
mentioning
confidence: 99%
“…Then, using immunohistochemistry approach authors found that TNF- was located mainly at the level of motor neurons and microglia. Some genes involved in apoptosis showed the same pattern of TNF- gene expression, suggesting a correlation between the inflammatory reaction and the apoptotic pathway (Yoshihara et al, 2002). To this regard, Hensley et al (2003) have characterized the relationship between the inflammatory genes, oxidative stress and apoptotic events in the G93A mice.…”
Section: Tnf- System and Alsmentioning
confidence: 96%
“…Although transcripts of both receptors, TNF-R1 and TNF-R2, have been identified in the spinal cord of the G93A rat (Elliot et al, 2001;Hensley et al, 2003). Yoshihara et al (2002) have shown that the expression of TNF- in the marrow of G93A mice overlaps with the activation of microglia already in a pre-symptomatic stage. Then, using immunohistochemistry approach authors found that TNF- was located mainly at the level of motor neurons and microglia.…”
Section: Tnf- System and Alsmentioning
confidence: 99%